Vulnerabilities in social anxiety: Integrating intra- and interpersonal perspectives - Ginat-Frolich, Rivkah; Gilboa-Schechtman, Eva; Huppert, Jonathan D.; Aderka, Idan M.; Alden, Lynn E.; Bar-Haim, Yair; Becker, Eni S.; Bernstein, Amit; Geva, Ronny; Heimberg, Richard G.; Hofmann, Stefan G.; Kashdan, Todd B.; et al. (Clinical Psychology Review, 2024)
What are the major vulnerabilities in people with social anxiety? What are the most promising directions for translational research pertaining to this condition? The present paper provides an integrative summary of basic and applied translational research on social anxiety, emphasizing vulnerability factors. It is divided into two subsections: intrapersonal and interpersonal. The intrapersonal section synthesizes research relating to (a) self-representations and self-referential processes; (b) emotions and their regulation; and (c) cognitive biases: attention, interpretation and judgment, and memory. The interpersonal section summarizes findings regarding the systems of (a) approach and avoidance, (b) affiliation and social rank, and their implications for interpersonal impairments. Our review suggests that the science of social anxiety and, more generally, psychopathology may be advanced by examining processes and their underlying content within broad psychological systems. Increased interaction between basic and applied researchers to diversify and elaborate different perspectives on social anxiety is necessary for progress.
CRIS-Team Scopus Importer:2024-04-05
Keywords: Basic research; Social anxiety; Social anxiety disorder; Translational research; Vulnerability